The Role of Global Competence in Addressing Challenges and Opportunities in International Business in the Era of Global Change - Yuwono, Matias Andika; Ellitan, Lena (CV. Ulil Albab Corp, 2024)
In today's interconnected world, global competence is vital for success in international business. Changes in technology, politics, economics, and social concerns have created a complex business environment. Global competence, which includes cultural awareness, adaptability, and strong communication skills, is essential for navigating this landscape. This article explores the importance of global competence in international management, how companies can develop it, and how ethical practices contribute to long-term success. It also emphasizes risk management, international collaboration, and the role of education in preparing individuals for the global workforce. By cultivating global competence, managing risks, and operating responsibly, companies can thrive in the ever-changing world of international business. The discussion in this article highlights the importance of proactive risk management, international collaboration, and the role of higher education institutions in preparing graduates with relevant global competencies. Companies can successfully navigate the dynamic global business landscape and achieve long-term success by developing global competence, managing risks proactively, and operating ethically and responsibly.